Clostridium ljungdahlii as a biocatalyst in microbial electrosynthesis – Effect of culture conditions on product formation. (September 2022) - Im, Chaeho; Valgepea, Kaspar; Modin, Oskar; Nygård, Yvonne
Abstract: Microbial electrosynthesis enables the production of value-added chemicals from CO2 and electrons provided by an electrode. Clostridium ljungdahlii is an electroactive acetogen that potentially could be used in microbial electrosynthesis systems. However, the optimal operational parameters for microbial electrosynthesis using C. ljungdahlii are not known. Here, we explored the effects of yeast extract, pH, and cathode potential. A low initial pH increased the rate of acetate production from CO2 and H2 in serum bottle cultures. When cultivated in bioelectrochemical systems, the optimal coulombic efficiency (i.e. close to 100 %) was observed at a cathode potential between −0.8 V and −1.0 V, while the highest productivity was reached at −1.0 V. Addition of yeast extract to the medium was needed to ensure reproducible results. Using cyclic voltammetry, we detected hydrogen-mediated extracellular electron transfer of C. ljungdahlii during growth on CO2 in a bioelectrochemical system. These results show that operational parameters should be chosen carefully to maximise the efficiency of microbial electrosynthesis. Graphical abstract: Unlabelled Image Highlights: Lower initial pH improved acetate production of C. ljungdahlii from H2 :CO2 . Yeast extract in the medium increased reproducibility of BES experiments. Different cathodic potentials were tested to find optimal operational conditions. The highest productivity in a BES with C. ljungdahlii was reached at −1.0 V. H2 mediated extracellular electron transfer was predominant for C. ljungdahlii .